Implementation of The Professional School Principal Selection Information System at The Bandung City Educational Office - Muhammad Taufiq; Fikri Aditya Tri Andikaputra (Trescode Green Organization, 2023)
School principal selection is a critical process to ensure educational quality through competent leadership. The Bandung City Education Office initiated the Professional School Principal Selection Information System (SIKASEP) as an online innovation to manage the administrative registration process from candidate training. This article aims to describe the implementation of the SIKASEP application, identify emerging obstacles, and outline resolution efforts. The method used was field observation and active participation during 30 days in the Secretariat Division. Results show that the SIKASEP application facilitated selection for 520 applicants across Kindergarten, Elementary, and Junior High levels. However, technical constraints were found, such as document upload failures due to low digital literacy, incorrect document placement, and network issues. Mitigation efforts included continuous socialization for teachers and periodic system updates to improve user-friendliness. This implementation successfully created a more organized and transparent selection process compared to the previous manual system.